The power of music : pioneering discoveries in the new science of song - Mannes, Elena (New York : Walker & Co., 2011)
This book is a pathbreaking exploration into how and why the human organism--and the ebb and flow of the cosmos--is moved by the undeniable effect of music. As Elena Mannes reveals in her eye-opening book, we are at a breakthrough moment in music research, for only recently has science sought in earnest to understand and explain the power of music and its connection to the body, the brain, and the world of nature. The award-winning creator of the acclaimed documentary The Music Instinct: Science and Song follows visionary researchers and accomplished musicians to unveil the latest discoveries in the new science of music. How much of our musicality is learned and how much is innate? Can examining the biological foundations of music help scientists unravel the intricate web of human cognition and brain function? Why is music virtually universal across cultures and time, and does it provide some evolutionary advantage? Can music make people healthier? Might music contain organizing principles of harmonic vibration that underlie the cosmos itself? One remarkable recent study shows that infants' cries contain common musical intervals. Physics experiments show that sound waves can change the structure of a material; world-famous musician Bobby McFerrin believes musical sound vibrations physically penetrate our bodies, shifting molecules as they do. From neurologist Gottfried Schlaug and X-ray astronomer Andrew Fabian, who studies the actual music of the spheres, to opera star Deborah Voigt and the deaf Scottish percussionist Evelyn Glennie, who "hears" through her feet, Mannes takes us to the crossroads of science and culture. Perhaps most remarkably, she explores the power of music to heal. "We can imagine a day," she writes, "when doctors write prescriptions for music," knowing what precise combinations of notes and styles affect different parts of the body and mind. - Publisher.
-- Table Of Contents: Foreword Aniruddh D. Patel Introduction: Music Matters Part I: The Musical Body And Brain Chapter 1 Feeling The Sound Chapter 2 Music Plays The Body Chapter 3 The Brain Plays Music Chapter 4 Is Music Our Genetic Birthright? Part II: The Musical Self Chapter 5 Agony And Ecstasy: How We Listen Chapter 6 Mind-Bending Notes: Can Music Make Us Smarter? Chapter 7 Music Speaks Chapter 8 Why Music? Part III: The Resonant World Chapter 9 Whale Songs, Elephant Bands, And Dancing Birds Chapter 10 The Music Of The Spheres Part IV: Music RX Chapter 11 Pain, Pills, or Music Chapter 12 The Next Wave? Chapter 13 Beyond The Concert Hall Acknowledgments Notes Bibliography Index
Includes bibliographical references and index.
Keywords: Music -- Psychological aspects; Music and science